PEMBIASAAN PELAKSANAAN PROGRAM PHBS PADA ANAK USIA DINI DI TK SYAFWAN DESA PEMATANG SIJONAM - Martini, Martini; Ahmad Syukri (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2024)
Early childhood is a vulnerable child aged 0 to 6 years. Refraction programs for early childhood are very important because they will have an impact on their future life. Refraction programs are efforts made by educators and education staff deliberately to develop good behavior (good attitude) which is based on the teacher's positive and negative understanding of behavior that is objectively recognized good for young children. This activity aims to increase the understanding of early childhood children at the Syafwan Kindergarten, Pematang Sijonam Village in terms of familiarizing themselves with implementing the PHBS program in their daily environment. The method of activity carried out is demonstration, namely an effort to provide information to children in order to realize behavior bias and increase understanding of the material presented in the process and implementation of learning activities.